ATRIBUT- ATRIBUT PRODUK YANG MEMPENGARUHI KONSUMEN DALAM MEMBELI DAGING SAPI DI GIANT EKPRES DINOYO MALANG - Numba, Melani Day Aba; Santoso, Erik Priyo; Sumarno, Sumarno; Murti, Ariani Trisna (Fakultas Pertanian, 2019)
This research was conducted on consumers who bought beef in Giant Ekspres Dinoyo, Malang. Data retrieval was carried out in May - June 2018 aimed at finding out the attributes of beef which had an effect on purchasing decisions. The sampling method used was a Purposive sampling method. The total population during the study amounted to 1000 respondents calculated using Slovin formula and got 90.9 respondents and rounded up to 100 respondents. The research variables were the meat fat content, meat fiber, meat water content, brand image, meat color, meat prices and the packaging of beef products. The research method used a descriptive quantitative method with technical data analysis using Statistical Product and Service Solutions (SPSS) computer program version 16.0. The results showed that 1) meat color, meat prices and product packaging were product attributes that significantly affected beef purchasing decisions, 2) other attributes (fat content, meat fiber, water content and brand image) had an effect but were not significant to the decision purchase of beef at Giant Ekpres Dinoyo Malang. Penelitian ini dilakukan pada konsumen yang membeli daging sapi di Giant Ekspres Dinoyo Malang. Pengambilan data dilakukan pada bulan mei – juni 2018 bertujuan untuk mengetahui atribut – atribut daging sapi yang berpengaruh terhadap keputusan pembelian. Metode pengambilan sampel yang digunakan adalah metode Purposive sampling. Total populasi selama penelitian berjumlah 1000 responden dihitung menggunakan rumus slovin sehingga mendapatkan 90,9 responden dibulatkan menjadi 100 orang responden. Variabel penelitian yang digunakan adalah kandungan lemak daging, serat daging, kandungan air daging, brand image (citra merek), warna daging, harga daging dan kemasan produk daging sapi. Metode analisis data yang digunakan adalah metode kuantitatif deskriptif dengan menggunakan program komputer Statistical Product and Service Solutions (SPSS) versi 16.0. Hasil penelitian menunjukkan bahwa 1) warna daging, harga daging dan kemasan produk merupakan atribut produk yang berpengaruh signifikan terhadap keputusan pembelian daging sapi, 2) atribut yang lain (kandungan lemak, serat daging, kadar air dan brand image) tidak berpengaruh terhadap keputusan pembelian daging sapi di Giant Ekpres Dinoyo Malang.